MARKETING 5.0 AND CONSUMER BEHAVIOR OF THE MILLENNIAL (GEN Z) GENERATION AS BUSINESS PERFORMANCE BOOSTING IN COVID-19 PANDEMIC (CASE STUDY: SMEs IN WEST JAVA) - Hermina, Nurul; Rahma, Yustika Dwi; Gusnia, Annisa Rahayu (CENTRAL ASIA AND THE CAUCASUS, 2022)
COVID- Pandemic 19 has been going on for more than eighteen months has given a very big shock to the Indonesian economy, especially SMEs. It is believed that the COVID-19 pandemic will not end shortly so the best way to do it is to synergize with the pandemic, one of which is by improving the performance of SMEs during the pandemic. To encourage the improvement of SME performance during the pandemic, it is very important to determine the right marketing strategy that pays attention to marketing 5.0 technology and also the consumer behavior of the millennial generation. The results of research involving SMEs in West Java using the partial least square path modeling structural equation model found that marketing 5.0 and consumer behavior of the millennial generation had a positive influence on marketing strategy and also on the marketing performance of SMEs in West Java.